Use of Subtractive Hybridization To Identify a Diagnostic Probe for a Cystic Fibrosis Epidemic Strain of Pseudomonas aeruginosa - Parsons, Yasmin N. (American Society for Microbiology (ASM), 2002)
A multiresistant strain of Pseudomonas aeruginosa is widespread among cystic fibrosis (CF) patients attending clinics in Liverpool, United Kingdom. Suppression subtractive hybridization was used to identify sequences present in the Liverpool CF epidemic strain but absent from strain PAO1. Using dot blot and PCR amplification assays, the prevalence of such sequences among a panel of CF isolates was determined. Several sequences were found only in the Liverpool epidemic strain. Some sequences were present in the Liverpool epidemic strain and in a minority of other isolates, including sequences with homology to genes implicated in O6 serotype and siderophore production. The Liverpool epidemic strain and 81% of nonepidemic isolates contained a sequence identified as part of the PAGI-1 genomic island. Other strains implicated in epidemic spread, which were from Manchester, United Kingdom, and Melbourne, Australia, were also screened. None of the sequences identified was present in the Manchester strain. However, one of two Melbourne strains contained some of the sequences found in the Liverpool epidemic strain. All isolates implicated in epidemic spread and 76% of sporadic isolates contained the exoS gene. A sequence present in all isolates of the Liverpool epidemic strain was used to develop a diagnostic PCR test for identification of the strain from colonies or directly from sputum samples.